Rose Rosette Disease: A New Disease of Roses in Florida - Binoy Babu; Mathews L. Paret; Tim Schubert; Carlye Baker; Gary Knox; Fanny Iriarte; James Aldrich; Laura Ritchie; Carrie L. Harmon; Svetlana Y. Folimonova (EDIS, 2015)
Rose rosette disease is an incurable, destructive disease that affects both wild and cultivated roses. Over the past several decades, the disease has spread over much of the U.S., though it was first observed in Florida in 2013. This 6-page fact sheet describes the symptoms and diagnosis of the disease, as well as the cultural, chemical, and, possibly, biological controls that can minimize its spread. Written by Binoy Babu, Mathews L. Paret, Tim Schubert, Carlye Baker, Gary Knox, Fanny Iriarte, James Aldrich, Laura Ritchie, Carrie L. Harmon, and Svetlana Y. Folimonova, and published by the UF Department of Plant Pathology, May 2015.